Biotic Factors in the Phytosanitary Technology of Green Pea Cultivation in the Trans-Urals - Porsev, Igor; Sozinov , Andrey; Polovnikova, Valentina; Vyunik, Anna (KnE Life Sciences, 2021)
This article presents the results of studying the phytosanitary situation in the cultivation of 10 varieties of green pea in the Trans-Urals. We noted that the economic threshold of harmfulness by the soilborne and leaf-and-stem disease agents was crossed in the majority of the varieties. All varieties of the peas were affected by root rot above the economic threshold of damage (15%). In 2018, the level of root rot development was 55.5% on average in the varieties, or an excess of EPR by 3.7 times; and in 2019, the development of rot was 44.6% or an excess of EPR by 3 times. High rates of Fusarium blight were evident in the Zauralskiy 4, Kulon, Krepysh, and Samarius varieties, and bacterial blight in the Krepysh and Tomas varieties. Rust development varied on average over the two years from 10.5% to 16.5%, and 12% of the standard cultivar Aksayskiy Usatii 55 was affected. 11% of Samarius 13% of Agrointel and 11.5% of Zauralskiy 3 were affected. For all varieties, the development of powdery mildew was below the economic threshold of harmfulness (EPV = 15%). A higher percentage of disease development was noted in the Zauralsky 4 variety (11.0%) and in the Yamalsky 305 variety (13.5%). The productivity of the seeds treated with chemical fungicide increased 1.2-1.9 times as compared to the reference sample. The productivity growth of the seeds treated with biofungicides amounted to 1.09-1.11 times the reference. The authors recommend a pre-sowing treatment of pea seeds with preparations of symbiotrophic nitrogen fixers (such as nitragin, rhizotorfin), combined with their treatment with microelements: ammonium molybdate with 50% content of the active ingredient (250 g / t of seeds) and boric acid (250-300 g / t of seeds). Keywords: green pea, varieties, diseases, fungicide, yield.This article presents the results of studying the phytosanitary situation in the cultivation of 10 varieties of green pea in the Trans-Urals. We noted that the economic threshold of harmfulness by the soilborne and leaf-and-stem disease agents was crossed in the majority of the varieties. All varieties of the peas were affected by root rot above the economic threshold of damage (15%). In 2018, the level of root rot development was 55.5% on average in the varieties, or an excess of EPR by 3.7 times; and in 2019, the development of rot was 44.6% or an excess of EPR by 3 times. High rates of Fusarium blight were evident in the Zauralskiy 4, Kulon, Krepysh, and Samarius varieties, and bacterial blight in the Krepysh and Tomas varieties. Rust development varied on average over the two years from 10.5% to 16.5%, and 12% of the standard cultivar Aksayskiy Usatii 55 was affected. 11% of Samarius 13% of Agrointel and 11.5% of Zauralskiy 3 were affected. For all varieties, the development of powdery mildew was below the economic threshold of harmfulness (EPV = 15%). A higher percentage of disease development was noted in the Zauralsky 4 variety (11.0%) and in the Yamalsky 305 variety (13.5%). The productivity of the seeds treated with chemical fungicide increased 1.2-1.9 times as compared to the reference sample. The productivity growth of the seeds treated with biofungicides amounted to 1.09-1.11 times the reference. The authors recommend a pre-sowing treatment of pea seeds with preparations of symbiotrophic nitrogen fixers (such as nitragin, rhizotorfin), combined with their treatment with microelements: ammonium molybdate with 50% content of the active ingredient (250 g / t of seeds) and boric acid (250-300 g / t of seeds). Keywords: green pea, varieties, diseases, fungicide, yield